2005
DOI: 10.1038/nature03215
|View full text |Cite|
|
Sign up to set email alerts
|

Postnatal isl1+ cardioblasts enter fully differentiated cardiomyocyte lineages

Abstract: The purification, renewal and differentiation of native cardiac progenitors would form a mechanistic underpinning for unravelling steps for cardiac cell lineage formation, and their links to forms of congenital and adult cardiac diseases. Until now there has been little evidence for native cardiac precursor cells in the postnatal heart. Herein, we report the identification of isl1+ cardiac progenitors in postnatal rat, mouse and human myocardium. A cardiac mesenchymal feeder layer allows renewal of the isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
930
2
28

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,205 publications
(988 citation statements)
references
References 24 publications
23
930
2
28
Order By: Relevance
“…Cardiac stem/progenitor cells expressing LIM homeodomain transcriptional factor Islet-1 (Isl-1 þ ) were recently identified by Laugwitz and colleagues (Laugwitz et al, 2005). These Isl-1 þ cells were isolated from very young animals, do not express c-kit but harbor cardiomyogenic potential both in vitro and in vivo.…”
Section: Isl-1 1 Cscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac stem/progenitor cells expressing LIM homeodomain transcriptional factor Islet-1 (Isl-1 þ ) were recently identified by Laugwitz and colleagues (Laugwitz et al, 2005). These Isl-1 þ cells were isolated from very young animals, do not express c-kit but harbor cardiomyogenic potential both in vitro and in vivo.…”
Section: Isl-1 1 Cscsmentioning
confidence: 99%
“…Mouse and human c-kit þ , CD31 þ , CD34 þ c-kit, CXCR4 Messina et al, 2004;Davis et al, 2009;Smith et al, 2007;Tang et al, 2009 Isl Laugwitz et al, 2005;Weinberger et al, 2012 CSCs, cardiac stem cells; CSP, cardiac side population.…”
Section: Cardiospheresmentioning
confidence: 99%
“…22 Laugwitz et al 23 demonstrated the presence of an Isl-1 + population of cardiac stem cells in the postnatal mouse, rat, and human heart, most prominently in the outflow tract and right atrium. Further studies showed that Isl-1 marks a population of multipotent cardiac stem cells contributing to smooth muscle, endothelial, and pacemaker cell lineages in the embryonic and postnatal heart 24,25 and implicate Isl-1 + Nkx2.5 + Flk-1 + cells as the most primitive cardiac stem cells.…”
Section: Isl-1 + Cardiac Stem Cellsmentioning
confidence: 99%
“…56,57 Another group of resident cardiac progenitor cells is characterized by the expression of the antigen 'islet 1' (isl1), and these isl1+ cells develop into cells with a mature cardiac phenotype including intact Ca 2+ -cycling and the generation of action potentials. 58 As mentioned earlier, SP cells can be isolated from the heart, and thus constitute a fifth cardiac progenitor phenotype that can acquire an adult cardiomyocyte phenotype when placed in a permissive environment. 42,43 Finally, cells have been isolated from myocyte depleted fractions of murine and human atria and ventricles that form spheres when cultured in 'cardiosphere growing medium'.…”
Section: Resident Cardiac Progenitor Cellsmentioning
confidence: 97%